Wheel Running Improves Motor Function and Spinal Cord Plasticity in Mice With Genetic Absence of the Corticospinal Tract - Zhang, Wei; Yang, Bin; Weng, Huandi; Liu, Tao; Shi, Lingling; Yu, Panpan; So, Kwok-Fai; Qu, Yibo; Zhou, Libing (Frontiers in Cellular Neuroscience, 2019)
Our previous studies showed that mutant mice with congenital absence of the corticospinal tract (CST) undergo spontaneous remodeling of motor networks to partially compensate absent CST function. Here, we asked whether voluntary wheel running could further improve locomotor plasticity in CST-deficient mice. Adult mutant mice were randomly allocated to a “runners” group with free access to a wheel, or a “non-runners” group with no access to a wheel. In comparison with non-runners, there was a significant motor improvement including fine movement, grip strength, decreased footslip errors in runners after 8-week training, which was supported by the elevated amplitude of electromyography recording and increased neuromuscular junctions in the biceps. In runners, terminal ramifications of monoaminergic and rubrospinal descending axons were significantly increased in spinal segments after 12 weeks of exercise compared to non-runners. EDU labeling showed that proliferating cells, 90% of which were Olig2-positive oligodendrocyte progenitors, were 4.8 fold more abundant in runners than in non-runners. In 8-week runners, RNAseq analysis of spinal samples identified 404 genes up-regulated and 398 genes down-regulated, and 69 differently expressed genes involved in signal transduction, among which the NF-kB, PI3K-Akt and cAMP signaling were three top pathways. Twelve-week training induced a significant elevation of postsynaptic density protein 95, synaptophysin 38 and myelin basic protein, but not of brain derived neurotrophic factor, glial cell line-derived neurotrophic factor and insulin like growth factor 1. Thus, locomotor training activates multiple signaling pathways, contributes to neural plasticity and functional improvement, and might palliate locomotor deficits in patients.